PELINDUNGAN HUKUM TERHADAP PENCIPTA KOMIK DIGITAL (WEBTOON) - Krisanty Jacomina Putri Numbery; Bernard Nainggolan; Johnson SMT Pangaribuan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The development of science and technology over time has been changed significantly. These significant developments have also led creators to create copyrighted works in digital form, including digital comics on the webtoon platform, digital comics on webtoon circulating without permission on illegal websites. This study aims to discuss the legal protection of creators of digital comics (webtoon), stating about copyright arrangements in digital comics and legal protection of copyright in digital comics (webtoon) in practice. This research uses normative juridical legal research methods with a statutory approach (the statue approach). From the results of this study it is concluded that copyright protection is given to copyrighted works which are then given exclusive rights to the creator as the copyright holder. Copyright infringement of digital comics such as piracy, duplication, translation, and distribution have legal consequences that have been regulated in Law Number 28 of 2014 concerning Copyright and other regulations related to copyright in digital comics.